Design and Virtual Performance Testing of the Accessory Equipment for a Left Ventricular Assist Device - Celik, Sinemis Z.; Kadipasaoglu, Kamuran (IEEE, 2025)
Cardiovascular diseases are the leading cause of global mortality, and heart failure remains a major consequence. While heart transplants are the gold standard for end-stage heart failure, donor shortages necessitate alternatives like left ventricular assist devices (LVADs). This study aimed to design and optimize the inlet and outlet cannulae and housing for an LVAD to minimize thrombosis risk and enhance device efficiency. Key design parameters included the diameters, lengths, and bend angles of the cannulae, ensuring smooth blood flow and reduced turbulence. Through iterative design modifications and computational fluid dynamics analysis, optimal configurations were identified. The results demonstrated that specific configurations significantly improved flow dynamics, reducing stagnant zones and wall shear stress. This study contributes to the development of a safer and more effective LVAD, addressing the critical need for mechanical circulatory support in patients with severe heart failure.
Keywords: Left Ventricular Assist Device; computational fluid dynamics; cannulae design; thrombosis risk; design optimization; hydraulic performance; Medical Informatics